Long term follow-up of Trypanosoma cruzi infection and Chagas disease manifestations in mice treated with benznidazole or posaconazole. - Claudia Magalhães Calvet; Tatiana Araújo Silva; Diane Thomas; Brian Suzuki; Ken Hirata; Jair Lage Siqueira-Neto; James H McKerrow (Public Library of Science (PLoS), 2020)
Chagas' Disease, caused by the protozoan parasite Trypanosoma cruzi, is responsible for up to 41% of the heart failures in endemic areas in South America and is an emerging infection in regions of North America, Europe, and Asia. Treatment is suboptimal due to two factors. First, the lack of an adequate biomarker to predict disease severity and response to therapy; and second, up to 120-days treatment course coupled with a significant incidence of adverse effects from the drug currently used. Because the disease can manifest itself clinically a few years to decades after infection, controversy remains concerning the suitability of current drug treatment (benznidazole), and the efficacy of alternative drugs (e.g. posaconazole). We therefore followed the clinical course, and PCR detection of parasite burden, in a mouse model of infection for a full year following treatment with benznidazole or posaconazole. Efficacy of the two drugs depended on whether the treatment was performed during the acute model or the chronic model of infection. Posaconazole was clearly superior in treatment of acute disease whereas only benznidazole had efficacy in the chronic model. These results have important implications for the design and analysis of human clinical trials, and the use of specific drugs in specific clinical settings.